Comparison of Intraocular Lens Power Calculation Methods Following Myopic Laser Refractive Surgery: New Options Using a Rotating Scheimpflug Camera - Cho, Kyuyeon; Lim, Dong Hui; Yang, Chan-min; Chung, Eui-Sang; Chung, Tae-Young (Korean journal of ophthalmology, 2018)
To evaluate and compare published methods of calculating intraocular lens (IOL) power following myopic laser refractive surgery. We performed a retrospective review of the medical records of 69 patients (69 eyes) who had undergone myopic laser refractive surgery previously and subsequently underwent cataract surgery at Samsung Medical Center in Seoul, South Korea from January 2010 to June 2016. None of the patients had pre-refractive surgery biometric data available. The Haigis-L, Shammas, Barrett True-K (no history), Wang-Koch-Maloney, Scheimpflug total corneal refractive power (TCRP) 3 and 4 mm (SRK-T and Haigis), Scheimpflug true net power, and Scheimpflug true refractive power (TRP) 3 mm, 4 mm, and 5 mm (SRK-T and Haigis) methods were employed. IOL power required for target refraction was back-calculated using stable post-cataract surgery manifest refraction, and implanted IOL power and formula accuracy were subsequently compared among calculation methods. Haigis-L, Shammas, Barrett True-K (no history), Wang-Koch-Maloney, Scheimpflug TCRP 4 mm (Haigis), Scheimpflug true net power 4 mm (Haigis), and Scheimpflug TRP 4 mm (Haigis) formulae showed high predictability, with mean arithmetic prediction errors and standard deviations of -0.25 ± 0.59, -0.05 ± 1.19, 0.00 ± 0.88, -0.26 ± 1.17, 0.00 ± 1.09, -0.71 ± 1.20, and 0.03 ± 1.25 diopters, respectively. Visual outcomes within 1.0 diopter of target refraction were achieved in 85% of eyes using the calculation methods listed above. Haigis-L, Barrett True-K (no history), and Scheimpflug TCRP 4 mm (Haigis) and TRP 4 mm (Haigis) methods showed comparably low prediction errors, despite the absence of historical patient information.